HISTOLOGICAL STUDIES OF THE EFFECTS OF ORAL ADMINISTRATION OF ASPILIA AFRICANA (ASTERACEAE) LEAF EXTRACT ON THE OVARIES OF FEMALE WISTAR RATS - Eweka, A. O. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Histological studies of the effects of oral administration of extract of Aspilia africana, used in ethno medical practice in Africa for the management of various ailments, on the ovarian tissues of matured female Wistar rats were studied. The rats (n=24), average weight 182g were randomly assigned into two treatment (n=16) and a control (n=8) group. The rats in the treatment groups received 0.5g/kg and 1g/kg of aqueous extract of Aspilia africana orally through orogastric tube for fourteen days, while the control rats received equal volume of distilled water without the extract of Aspilia added. The rats were fed with growers’ mash and were given water liberally. The rats were sacrificed on day fifteen of the experiment. The ovary was carefully dissected out and quickly fixed in 10% formal saline for routine histological study after H&E method. The histological findings indicated that the treated sections of the ovary showed cellular hypertrophy of the theca folliculi, distortion of the basement membrane, degenerative and atrophic changes in the oocyte and zona granulosa. There were marked vacuolations appearing in the stroma cells. These findings indicate that Aspilia africana consumption may probably have adverse effects on the ovaries by its deleterious effects on the oocytes and stroma cells of ovary of adult Wistar rats. It is recommended that further studies aimed at corroborating these observations be conducted.